New Horizons in Laparoscopic Surgery - Ferhat Ferhatoglu, Murat (IntechOpen, 2018)
Approximately 100 years ago, after the first diagnostic laparoscopy and subsequent developments, the adventure began with laparoscopic appendectomy and cholecystectomy and reached a point where any surgical procedure could be performed easily. Today, many endoscopic surgical procedures have an important role not only in general surgery, but also in the daily practice of many surgical branches. This vertiginous development and change of speed make rapid replacement of the visual and printed materials necessary for training in this area. This book is prepared by surgeons who are very successful in their field.